Pertanggungjawaban Pidana Rumah Sakit Terhadap Pengelolaan Limbah Medis B3 Penanganan Pandemi Covid-19 Di Indonesia - Fikri Adrian; Fadillah Sabri (Fakultas Hukum Universitas Andalas, 2023)
Environmental problems are becoming increasingly serious over time. The Covid-19 pandemic that hit Indonesia did not reduce the impact of environmental pollution but instead gave rise to a new problem, namely medical B3 waste. Of course, B3 medical waste produced by hospitals must be clear regarding its management, sanctions and implementation of law enforcement. Because the impacts can affect the environment and public health. The research method used is normative legal research (normative juridical) using a statutory approach (Status Approach) and a Conceptual Approach (Conceptual Approach). Corporate/hospital criminal liability for violations of B3 waste management is regulated in Article 116 Jo 118 of the PPLH Law. Article 116 paragraph (1) letter a of the PPLH Law states that business entities can be prosecuted criminally, but in Article 118, in the case of charges against business entities, the representative management is the functional actor. Apart from the main criminal penalties, business entities may be subject to additional criminal/disciplinary regulations based on Article 119 of the PPLH Law. Based on research, there are weaknesses in the PPLH Law regarding corporate responsibility, namely first, corporate responsibility does not guarantee legal certainty. Second, there is no distinction between basic criminal sanctions for human and corporate legal subjects